2018
DOI: 10.11604/pamj.2018.29.157.10151
|View full text |Cite
|
Sign up to set email alerts
|

Early feeding practices and stunting in Rwandan children: a cross-sectional study from the 2010 Rwanda demographic and health survey

Abstract: Introductionin Rwanda, despite different interventions to improve child nutrition status, malnutrition in children under five years of age continue to be a public health concern. This study aimed to evaluate the factors that contribute to childhood stunting by assessing feeding practices of Rwandans in children ≤ 2 years of age.MethodsA cross-sectional study with data obtained from the 2010 Rwanda Demographic and Health Survey was conducted on 1,634 children ≤ 2 years of age with complete anthropometrical meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
1
15
0
2
Order By: Relevance
“…The prevalence of stunting in this population was high, with 26% of children aged 6-23 months affected, and this level of stunting in Central Jakarta is categorised as a moderate public health problem by WHO (1995). The prevalence of stunting was higher in children aged 12-23 months than in children aged 6-11 months, and this finding is similar to results from Rwanda (Nsereko, 2018). As children age, their growth curve deviates from the normal curve in line with the increase in their nutritional needs (Terati & Susanto, 2018).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The prevalence of stunting in this population was high, with 26% of children aged 6-23 months affected, and this level of stunting in Central Jakarta is categorised as a moderate public health problem by WHO (1995). The prevalence of stunting was higher in children aged 12-23 months than in children aged 6-11 months, and this finding is similar to results from Rwanda (Nsereko, 2018). As children age, their growth curve deviates from the normal curve in line with the increase in their nutritional needs (Terati & Susanto, 2018).…”
Section: Discussionsupporting
confidence: 67%
“…The results of this study showed that children who did not meet MAD were 3.29 times more likely to be stunted. The fulfilment of MAD is therefore very important because it represents the effect of both food quantity and quality on children's linear growth (Nsereko, 2018). A cohort study conducted in Bangladesh found that the fulfilment of MAD was a predictor of linear growth in children aged 6-24 months (Owais et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies on the risk factors underlying child undernutrition in Rwanda have mainly focused on socio-economic and demographic factors (13)(14)(15)(16) . Other studies (17)(18)(19) examined the influence of access to health care on child stunting.…”
mentioning
confidence: 99%
“…In contrast to the results of the research by Bertalina and Amelia (2018) stated that there was no relationship between exclusive breastfeeding and the incidence of stunting. Supported by research conducted on children less than two years in Rwanda that exclusive breastfeeding was not associated with the incidence of stunting because exclusive breastfeeding was a factor of protection against stunting but did not address other factors such as nutritional deficiencies, infections and diarrhea (Nsereko et al , 2018) . Other studies are also different namely research conducted on 6,956 children aged 6-23 months in Indonesia that exclusive breastfeeding was not associated with the incidence of stunting due to limited secondary data so that it cannot be clearly distinguished exclusive breastfeeding ≥ 6 months with exclusive 6 months ASI (Paramashanti et al, 2015).…”
Section: Relationship Of Exclusive Breastfeeding Withstuntingeventsinmentioning
confidence: 99%